2022
DOI: 10.4049/jimmunol.2100049
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemic Zika Virus Isolate Drives Enhanced T Follicular Helper Cell and B Cell–Mediated Immunity

Abstract: Zika virus (ZIKV) is a mosquito-borne pathogen that recently caused a series of increasingly severe outbreaks. We previously demonstrated that, compared with a pre-epidemic isolate (ZIKVCDN), a Brazilian ZIKV isolate (ZIKVBR) possesses a novel capacity to suppress host immunity, resulting in delayed viral clearance. However, whether ZIKVBR modulates CD4 T cell responses remains unknown. In this study, we show that, in comparison with ZIKVCDN infection, CD4 T cells are less polarized to the Th1 subtype followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The affinity-ELISA assay was conducted as described in a previous study. 41 Briefly, based on the above protocol, various concentrations of ammonium thiocyanate (0.15–4 M range) were added into the wells and incubated for 15 min prior to adding the IgG incubation. The plates were developed with TMB substrate solution (Thermo Scientific, Cat: 34021) and quenched with 2N sulfuric acid prior to measurement at 450nm with a microplate reader (BioTek).…”
Section: Star*methodsmentioning
confidence: 99%
“…The affinity-ELISA assay was conducted as described in a previous study. 41 Briefly, based on the above protocol, various concentrations of ammonium thiocyanate (0.15–4 M range) were added into the wells and incubated for 15 min prior to adding the IgG incubation. The plates were developed with TMB substrate solution (Thermo Scientific, Cat: 34021) and quenched with 2N sulfuric acid prior to measurement at 450nm with a microplate reader (BioTek).…”
Section: Star*methodsmentioning
confidence: 99%
“…Pardy et al showed that CD4 + T cells were differentially polarized to the Th1 subtype after challenging mice with pre-epidemic or contemporary ZIKV strains. The differences were characterized by enhanced GC B cell response and robust production of higher avidity-nAbs following the infection with the contemporary strain, suggesting that ZIKV strains have evolved to differentially induce T cell, B cell, and Ab responses including their avidity and neutralization properties (Pardy et al, 2022). These results are relevant while considering ZIKV vaccine designs.…”
Section: Discussionmentioning
confidence: 99%
“…These cells have been described, in terms of function, as the equivalent counterpart of germinal center (GC) Tfh cells in peripheral blood (Bentebibel et al, 2013; Crotty, 2014; Morita et al, 2011). However, there is limited literature available on the role of pTfh cells in DENV (Haltaufderhyde et al, 2018; Izmirly et al, 2022; Wijesinghe et al, 2020) and ZIKV vaccination or infections (Liang et al, 2019; Pardy et al, 2022). Despite their critical role helping B cells form an optimal humoral immune response, there are scarce works studying the direct interactions of CD4 + T cells/pTfh cells subsets with B cells and NS proteins, and its effect in Abs functionality against DENV and/or ZIKV (Elong Ngono et al, 2019; Rivino et al, 2013; Rouers et al, 2021).…”
Section: Introductionmentioning
confidence: 99%